2020
DOI: 10.1186/s13000-020-01048-1
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0001421 facilitates glycolysis and lung cancer development by regulating miR-4677-3p/CDCA3

Abstract: Background Lung cancer (LC) is a malignant tumor originating in the bronchial mucosa or gland of the lung. Circular RNAs (circRNAs) are proved to be key regulators of tumor progression. However, the regulatory effect of circ_0001421 on lung cancer tumorigenesis remains unclear. Methods The expression levels of circ_0001421, microRNA-4677-3p (miR-4677-3p) and cell division cycle associated 3 (CDCA3) were detected by quantitative real-time polymerase chain reaction (qRT-PCR). Methyl thiazolyl tetrazolium (MTT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The clinical application of immunotherapy has shifted the focus of tumor treatment from tumor cells to the tumor microenvironment (27). Based on CIBERSORT bioinformatics analysis, our study found that 14 of 22 types of immune cells had significant differences in the high and low CDCA3 expression groups, including memory B cells, activated mast cells (P<0.05), follicular helper T cells, 4677-3p/CDCA3 axis is a ceRNA network that boosts proliferation and migration in HCC, BC, and LC (21,30,31). LncRNA LINC00707 accelerates the development and progression of BC by targeting miR-145/CDCA3 (22).…”
Section: Discussionmentioning
confidence: 80%
“…The clinical application of immunotherapy has shifted the focus of tumor treatment from tumor cells to the tumor microenvironment (27). Based on CIBERSORT bioinformatics analysis, our study found that 14 of 22 types of immune cells had significant differences in the high and low CDCA3 expression groups, including memory B cells, activated mast cells (P<0.05), follicular helper T cells, 4677-3p/CDCA3 axis is a ceRNA network that boosts proliferation and migration in HCC, BC, and LC (21,30,31). LncRNA LINC00707 accelerates the development and progression of BC by targeting miR-145/CDCA3 (22).…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, CDCA3, which encodes cell division cycle associated protein-3, is also found to be increased in NSCLC tissues and associated with poor patient prognosis [ 27 ]. Zhang et al reported that CDCA3 is regulated by miR-4677-3p during lung cancer development [ 60 ]. Four other genes involved in the ceRNA network, including MCM7 [ 29 ], NCAPG2 [ 31 ], SETD6 [ 34 ], and KIF22 [ 35 ] have also been reported to involved in lung cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…This circRNA-miRNA-mRNA regulatory axis has been identified in a variety of human cancer cells [20]. For instance, circ_0001421 promotes glycolysis and lung cancer development by regulating miR-4677-3p to upregulating cell division cycle associated 3 (CDCA3) [37]. Circ_0084927 sponges miR-142-3p and up-regulates ADP ribosylation factor like GTPase 2 (ARL2) to aggravate the proliferation of cervical cancer cells [38].…”
Section: Discussionmentioning
confidence: 99%